Paradoxes of an Image: A Pictorial or Postsecular Turn? - Daraškevičiūtė, Vaiva (Religija ir kultūra, 2019)
The article discusses the interaction between religion and art, focusing on contemporary visual theories, especially on the concept of vitality of image, formulated by such authors as David Freedberg, Thomas William Mitchell and Horst Bredekamp. The article states that the aspect of immediate fate (in the sense of pathos), which is emphasized in the concept of vitality of image, opens up the possibility to discuss the postsecular approach of the pictorial turn (Mitchell). The article recalls a recent situation in one of the Vilnius (Lithuania) churches, when the original sculpture of St. Virgin Mary, created by Lithuanian artist Ksenija Jaroševaitė, was replaced by the copy of widely circulated sculpture of St. Mary of Lourdes, originally created in 1864 by French sculptor Joseph-Hugues Fabisch, at the request of the churchgoers. In the article the latter situation also serves as a representative model, revealing the paradoxicality of an image, when the aesthetic judgement is changed by the unreflected recognition of the power of the image. The article discusses the problem of the ontological status of an image, admitting that the condition of emancipation of the image implicated in the concept of its vitality leads to the condition of the uncanny and questions related to such fundamental controversies as distinctions between creator and image or vitality and artefact.
Keywords: image; vitality of image; uncanny; pictorial turn; postsecularity